Identification of a Conserved Sequence in Flavoproteins Essential for the Correct Conformation and Activity of the NADH Oxidase NoxE of Lactococcus lactis - Tachon, Sybille (American Society for Microbiology, 2011)
Water-forming NADH oxidases (encoded by noxE, nox2, or nox) are flavoproteins generally implicated in the aerobic survival of microaerophilic bacteria, such as lactic acid bacteria. However, some natural Lactococcus lactis strains produce an inactive NoxE. We examined the role of NoxE in the oxygen tolerance of L. lactis in the rich synthetic medium GM17. Inactivation of noxE suppressed 95% of NADH oxidase activity but only slightly affected aerobic growth, oxidative stress resistance, and NAD regeneration. However, noxE inactivation strongly impaired oxygen consumption and mixed-acid fermentation. We found that the A303T mutation is responsible for the loss of activity of a naturally occurring variant of NoxE. Replacement of A303 with T or G or of G307 with S or A by site-directed mutagenesis led to NoxE aggregation and the total loss of activity. We demonstrated that L299 is involved in NoxE activity, probably contributing to positioning flavin adenine dinucleotide (FAD) in the active site. These residues are part of the strongly conserved sequence LA(T)XXAXXXG included in an alpha helix that is present in other flavoprotein disulfide reductase (FDR) family flavoproteins that display very similar three-dimensional structures.